Pelatihan dengan Pendekatan Behavioral Skill pada Peningkatan Keterampilan - Salix Fini Maris (Eastasouth Institute, 2023)
Basically training has the intention to bring about permanent positive changes in individual attitudes, awareness, and skills. Permanent positive changes are closely related to the habits (behavior) of individuals implementing their skills. The purpose of this study is to review published articles that explain how behavioral skill training affects skills improvement. In his review considers the behavioral aspects of skills in training and their relationship with mindfulness and mental models to be associated with skill improvement. The research approach that will be carried out is through a literature review of frequency analysis or mapping. This method analyzes emerging trends in all published articles reviewed. The results of the review will be able to elaborate existing studies to be interpreted into various trainings.